2013
DOI: 10.1074/jbc.m112.413195
|View full text |Cite
|
Sign up to set email alerts
|

Role of 4-Hydroxybutyrate-CoA Synthetase in the CO2 Fixation Cycle in Thermoacidophilic Archaea

Abstract: Background: Thermoacidophilic Sulfolobales contain a novel CO 2 fixation pathway; all enzymes but one have been accounted for in Metallosphaera sedula. Results: Enzymes encoded in Msed_0394 and Msed_0406 each exhibit 4-hydroxybutyrate-CoA synthetase activity, consistent with transcriptomic evidence. Conclusion: Msed_0406 is likely the physiologically relevant enzyme in the cycle. Significance: All enzymes are now accounted for in the CO 2 fixation cycle of M. sedula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 44 publications
0
39
0
1
Order By: Relevance
“…Cell extract measurements revealed that the two CoA ligases acting on 3-hydroxypropionate and 4-hydroxybutyrate were ADP-forming ( Fig. 1 and Table 1), whereas aerobic Crenarchaeota possess AMP-forming ligases (19,30,31). Because this issue is important for evaluating the energy efficiency of the cycle, we studied these enzymes in greater detail.…”
Section: Characterization Of Previously Unidentified Enzymes Involvedmentioning
confidence: 99%
“…Cell extract measurements revealed that the two CoA ligases acting on 3-hydroxypropionate and 4-hydroxybutyrate were ADP-forming ( Fig. 1 and Table 1), whereas aerobic Crenarchaeota possess AMP-forming ligases (19,30,31). Because this issue is important for evaluating the energy efficiency of the cycle, we studied these enzymes in greater detail.…”
Section: Characterization Of Previously Unidentified Enzymes Involvedmentioning
confidence: 99%
“…The Sulfolobales-specific training set included the HHC pathway genes that were significantly upregulated under autotrophic conditions in the transcriptomic analyses of M. sedula (7,14) (see Table S1 in the supplemental material). For the Thermoproteales group, the training set included the DHC pathway genes from the comparative proteome and enzyme activity studies of autotrophically and heterotrophically grown cells of T. neutrophilus (15), including Tneu_0418 to Tneu_0422, Tneu_1797 to Tneu_1795, and Tneu_1204.…”
Section: Bioinformatics Tools and Databasesmentioning
confidence: 99%
“…Indeed, microarray transcriptional response analysis of M. sedula showed significant upregulation of the characteristic HHC enzymes under au-totrophic versus heterotrophic conditions (7,14). However, the mechanism of transcriptional regulation of the HHC pathway in the Sulfolobales is currently unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations